Pathologic Response to Preoperative Chemotherapy - Blazer III, Dan (2008)
Purpose The primary goal of this study was to evaluate whether pathologic response to chemotherapy predicts patient survival after preoperative chemotherapy and resection of colorectal liver metastases (CLM). The secondary goal of the study was to identify the clinical predictors of pathologic response. Patients and Methods A retrospective review was performed of 305 patients who underwent preoperative irinotecan- or oxaliplatin-based chemotherapy, followed by resection of CLM. Pathologic response was systematically evaluated and reported as the mean of the percentage of cancer cells remaining within each tumor. Univariate and multivariate analyses were performed to identify the predictors of pathologic response and survival. Results Cumulative 5-year overall survival rates by pathologic response status were as follows: 75% complete response (no residual cancer cells), 56% major response (1% to 49% residual cancer cells), and 33% minor response (≥ 50% residual cancer cells; complete v major response, P = .037; major v minor response, P = .028). Multivariate analysis revealed that only surgical margin status (P = .050; hazard ratio [HR], 1.77) and pathologic response (major response: P = .034; HR, 4.80; minor response: P = .007; HR, 6.93) were independent predictors of survival. Multivariate analysis of the predictors of pathologic response revealed that carcinoembryonic antigen level ≤ 5 ng/mL, tumor size ≤ 3 cm, and chemotherapy with fluoropyrimidine plus oxaliplatin and bevacizumab were independent predictors of pathologic response. Conclusion Pathologic response predicts survival after preoperative chemotherapy and resection of CLM. Degree of pathologic response represents a new outcome end point for prognosis after resection of CLM.